1994
DOI: 10.1152/jappl.1994.77.3.1081
|View full text |Cite
|
Sign up to set email alerts
|

Protein accumulation in cerebrospinal fluid during -90 degrees head-down tilt in rabbit

Abstract: Plasma proteins are only somewhat larger than the intercellular spaces of the cerebral microvessels that constitute the blood-brain barrier or of the choroid plexus villi that elaborate cerebrospinal fluid (CSF). We hypothesized that the integrity of these barriers in anesthetized rabbits might be compromised during head-down tilt (HDT). Plasma protein and osmolality, hematocrit, and CSF protein concentration were compared in rabbits exposed to 1 h of HDT (n = 20) and prone rabbits (n = 10). In addition, the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…Thus, we have to take account of species difference for analyzing the effect of HDT. Since plasma leakage has been reported to occur within 1 h of 90°HDT in rabbits [30], the failure to form edema in the present study may be attributable to the angle of HDT but not to the period of HDT. In a previous study, we demonstrated an angledependent change in intracranial pressure during HDT [9].…”
Section: Discussionmentioning
confidence: 44%
See 1 more Smart Citation
“…Thus, we have to take account of species difference for analyzing the effect of HDT. Since plasma leakage has been reported to occur within 1 h of 90°HDT in rabbits [30], the failure to form edema in the present study may be attributable to the angle of HDT but not to the period of HDT. In a previous study, we demonstrated an angledependent change in intracranial pressure during HDT [9].…”
Section: Discussionmentioning
confidence: 44%
“…Wen et al [30] showed that disruption of the blood-cerebrospinal fluid barrier occurred during 90°HDT in rabbits. Parazynski and coworkers [5] demonstrated elevation of the capillary pressure in the human head during HDT.…”
Section: Discussionmentioning
confidence: 99%
“…As recently reviewed in detail [137], this route of cerebral venous drainage has had, since its discovery well over a century and a half ago, a most complex and interesting history, and more recently application, in medical advances. Contemporary awareness of the potential of this route began when researchers in aviation medicine were exploring an animal model of the effects of gravity and body position on pilots of high-performance aircraft [138]. They noted that restraining anesthetized rabbits on a tilt board and rotating them to a head-down position considerably increased CSF levels of the plasma protein albumin within 5 min.…”
Section: Blood-brain Barrier (Bbb) Passage By Specific Anti-tnf Biolomentioning
confidence: 99%
“…Its logic depends on 1) a short period of head-down tilting to gain a gravitational advantage, 2) an awareness of anatomy of Batson's plexus [a valveless venous system that surrounds the spinal column in continuum with the choroid plexus (Nathoo et al, 2011)], and 3) knowledge of the effect of acute hypertension on choroid plexus permeability [a 30-fold increase in albumin in CSF within 10 min of pharmacologically induced acute local hypertension (Murphy and Johanson, 1985)]. Not surprisingly, therefore, the gravitational effect on this valveless blood column of a 5-min head-down tilt of head and trunk has been reported, in anesthetized rabbits, to increase dramatically the passage of albumin and globulin, molecules of etanercept size, from plasma to the cerebrospinal fluid (Wen et al, 1994). The authors noted that this would be a useful way to get large molecules into the CSF for therapeutic purposes.…”
Section: A Specific Inhibition Of Tumor Necrosis Factormentioning
confidence: 99%